ANALISIS FINANCIAL DISTRESS DENGAN ACCOUNTING RATIO DAN FORECASTING BANKRUPCY TERHADAP PERUSAHAAN PERBANKAN GO PUBLIC DI INDONESIA - Rihardhiny Nariswari Putri; Djuminah Djuminah (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2017)
This study aims to analyze the prediction level of bankruptcy by the method of Altman Z Score on banking companies Go Public during the year 2010-2014, the prediction of performance by using intellectual capital in companies that Go Public during the year 2010-2014 and the influence between intellectual capital against the risk of bankruptcy on Go Public companies are battling for 2010-2014.This research uses quantitative method to know its direct effect. Meanwhile, to analyze the risk of bankruptcy using Altman Z-Score and to analyze intellectual capital using VAIC.The results of this study are a) During 2010 - 2014 the average banking indicated bankrupt 43.45%, 50.34% gray, and not bankrupt 6.21%. B) The average value of intellectual capital in 2010-2014 with the top category of 24.14%, good as much as 38.62%, common as much as 28.28% and bad as much as 8.97%. Thus it can be said that intellectual capital of banking in Indonesia is relatively good to support company performance. C) There is a significant negative influence between intellectual capital against bankruptcy risk. Keywords: Bankruptcy, Intellectual Capital